Augmenting Early Childhood Speech Skills through Audiovisual Talk Time Playing (ATTP): A Research & Development Approach - Saodi, Syamsuardi; Herlina, Herlina; Rusmayadi, Rusmayadi; Sadaruddin, Sadaruddin; Hasmawaty, Hasmawaty (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This study focused on developing, validating, and evaluating the effectiveness of the Audiovisual Talk Time Playing (ATTP) model for enhancing speech skills in 5-6-year-old children within a kindergarten environment. Employing research with development methodology, this study followed Plomp's (1997) framework through four phases: design, realization/construction, testing, evaluation, and implementation. The ATTP model was developed through a detailed analysis and synthesis of requirements for fostering young learners' speaking skills. Its practical application involved translating the theoretical model into a classroom with 15 children. The model's effectiveness was evaluated using validation sheets, model assessments, usability sheets, observation sheets, teacher questionnaires, and student learning outcome evaluation sheets. Qualitative data was collected through observations and teacher questionnaires, while quantitative data was derived from assessments of children's speaking abilities. The results indicated a significant improvement in children's communication skills, with an increased percentage of children moving from 'adequate' to 'good' speech skills categories. Educators responded positively to the ATTP model, emphasizing its practicality and effectiveness. The study concluded that the ATTP model, with its interactive and multisensory approach, is a more engaging and effective method for language development in early childhood education than traditional methodologies. However, the study's limited focus on a specific age group and setting suggests the need for future research to explore the model's long-term impacts and adaptability in different educational contexts.